Evaluasi Usability Testing Aplikasi Vidio dengan Menggunakan Metode Usability Testing - Amren Rahul Satria Harianja; M. Fahreza; Khairul Ihsan (Jurnal Teknik dan Teknologi Indonesia, 2023)
Vidio application is a video streaming application platform that finds many interesting features. The Vidio application has several advantages and disadvantages, which can be seen in user comments on this application in the playstore. It is necessary to analyze the level of user satisfaction with the Vidio application. The data collection technique uses task scenarios and through the SUS questionnaire distributed to users of the Vidio application, to collect and analyze data on user satisfaction with the Vidio application. The method used to analyze the data is using the Usability Testing method. The results of the evaluation on the Vidio application show an efficiency value of 89% in the efficiency aspect, the memorability aspect has a good memory level, the learnability aspect shows an effectiveness value of 97%, and in the satisfaction aspect the Vidio application gets a range of f values